DFIG Based AGC of Power System Using Robust Methodology. (May 2017) - Sharma, Gulshan; Ibraheem,; Bansal, R.C.
Abstract: The electrical energy system size is increasing and getting complex day by day with rising trends to integrate renewable energy sources like wind power in order to deliver the economic energy to the modern and developing society. However, the rising trends of wind energy generation and involvement raises serious concern for matching the generations with load demand and hence to maintain the standards of automatic generation control (AGC). Therefore, the power system needs robust design techniques for such type of complex system. This paper discusses the robust methodology for AGC of conventional system with sufficient contribution from doubly fed induction generator (DFIG) in control areas. The robust AGC are applied on the above said complex system and the application results are compared with control design based on optimal theory in terms of system stability and the achieved responses to validate the influence of the proposed technique.